Budget Impact of RefluxStop™ as a Treatment for Patients with Refractory Gastro-oesophageal Reflux Disease in the United Kingdom - Sam Harper; Lukasz Grodzicki; Stuart Mealing; Elizabeth Gemmill; Paul Goldsmith; Ahmed Ahmed (Journal of Health Economics and Outcomes Research)
**Background:** Gastro-oesophageal reflux disease (GORD) is a common condition associated with heartburn and regurgitation. Standard of care for GORD patients in the UK involves initial treatment with proton pump inhibitors (PPIs) and laparoscopic antireflux surgery in patients unwilling to continue or intolerant of long-term PPI treatment. Recently, RefluxStop™, a novel, implantable medical device, has proven to be an efficacious and cost-effective treatment for patients with GORD. The current analysis aimed to describe the budget impact of introducing RefluxStop™ within National Health Service (NHS) England and Wales.